1991
DOI: 10.1210/endo-128-1-526
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-Dependent in Vitro Stimulation of Adrenocortical Steroidogenesis by Interleukins*

Abstract: The effects of interleukins on adrenal steroidogenesis and their mode of action were studied using cultured rat adrenal cells. The addition of rat interleukin-1 alpha (IL-1 alpha) or rat IL-2 increased corticosterone levels in the medium in a concentration-dependent manner during 24 h of incubation. The minimum, half-maximum, and maximum effective concentrations of both rat IL-1 alpha and rat IL-2 were almost same (approximately 3, 10, and 100 U/ml, respectively). After a latent period, the effect became appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
2
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(71 citation statements)
references
References 0 publications
0
67
2
2
Order By: Relevance
“…One pathogenic mechanism might relate to perturbations in the homeostatic interplay between the HPA axis and the immune system, in the form of cytokines (Jenkins and Grossman, 1997). It has been clearly established that interleukins (ILs) 1α, IL-1ÎČ, IL-6 and IL-2 are all able to exert a direct stimulatory effect on adrenocortical cortisol secretion (Roh et al, 1987;Whitcomb et al, 1988;Salas et al, 1990;Tominaga et al, 1991;O'Connell et al, 1994), with the stimulatory effects of IL-1α and IL-1ÎČ being suggested to be mediated via prostaglandins (PGD 2 , PGF 2 and PGE 2 ) (Winter et al, 1990;Tominaga et al, 1991). Furthermore, IL-6 has been shown to act synergistically with physiological concentrations of ACTH in stimulating cortisol secretion (Salas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…One pathogenic mechanism might relate to perturbations in the homeostatic interplay between the HPA axis and the immune system, in the form of cytokines (Jenkins and Grossman, 1997). It has been clearly established that interleukins (ILs) 1α, IL-1ÎČ, IL-6 and IL-2 are all able to exert a direct stimulatory effect on adrenocortical cortisol secretion (Roh et al, 1987;Whitcomb et al, 1988;Salas et al, 1990;Tominaga et al, 1991;O'Connell et al, 1994), with the stimulatory effects of IL-1α and IL-1ÎČ being suggested to be mediated via prostaglandins (PGD 2 , PGF 2 and PGE 2 ) (Winter et al, 1990;Tominaga et al, 1991). Furthermore, IL-6 has been shown to act synergistically with physiological concentrations of ACTH in stimulating cortisol secretion (Salas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 induced corticosteroid biosynthesis in vivo independently from ACTH and caused glucocorticoid secretion in hypophysectomized rats (55), perfused rat adrenals (56), and dispersed human adrenal cells (57). IL-6 stimulated corticosterone release from rat adrenocortical cells alone and in synergy with ACTH, an effect probably mediated and amplified by PGs (58). Recombinant human IL-6 also increased the secretion of cortisol and adrenal androgens in humans both via ACTH and directly.…”
Section: Immune-adrenal Interactionsmentioning
confidence: 99%
“…It is of value to be indicated that IL-2 used in this study was at the half-maximum effective concentration which induced corticosterone biosynthesis in our previous adrenal cell culture study [12]. In this study, we compared the time courses of IL-2 stimulated prostaglandin E2, cyclic AMP and corticosterone synthesis in dispersed rat adrenal cells and found that prostaglandin E2 synthesis began to increase within an hour but the stimulation of cyclic AMP and corticosterone synthesis needed more than 12 hr to be induced [27]. Why steroidogenesis requires a relatively long latent period after the initial cellular change, i.e., prostaglandin E2 synthesis is one of the major unanswered questions in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Primary cultures of enzymatically dispersed rat anterior pituitary cells and adrenal cells were prepared as described previously [27], except that the cells were plated on glass coverslips at a density of 2 x 105 cells. All experiments were done 3 days after plating.…”
Section: Cell Preparationmentioning
confidence: 99%
See 1 more Smart Citation